Expression of emotional intelligence among tennis players - Dumciene, A.; Bileviciene, S.; Sipaviciute, B. (Baltic Journal of Sport and Health Sciences, 2020)
Background. Emotional intelligence (EI) is most commonly studied based on the cognitive-emotional ability or trait emotional self-efficacy model (Siegling & Petrides, 2015). This study was based on the EI capability model. Research based on ability models measures a person`s ability to solve emotional problems and assesses the ability to perform emotion-related tasks (Magrum, Waller, Campbell, & Schempp, 2019). The aim of this study was to reveal the expression of emotional intelligence in tennis players.